A multiple perspective approach towards the assessment and development of expert systems in manufacturing. Volume 1 - Holden, Peter D. (Cranfield Institute of Technology, 1991)
Current approaches to technology innovation often fail because they are conceived and assessed from a single perspective or dimension. Thus, current considerations in expert systems development are characterised by a strong focus upon the technology and technical issues without a prior process of wider appraisal and technology assessment. A central theme of this study is that the business, organisational and human factors, which determine how effectively the technology will be used in practice, must be an integral part of the assessment process. The thesis describes a ‘multiple perspective approach’ to technology assessment applied to expert systems innovation in a large manufacturing organisation. This research therefore embraces detailed technical, organisational and individual perspectives of expert systems assessment and development and describes how each perspective adds new concepts, methods and tools. In practice, this has meant modelling activities and information flows in a two-site manufacturing organisation, the identification of a variety of potential areas for expert systems development, the narrowing down and selection of particular areas according to technical, organisational, business and personal criteria, and the eventual design, development, ‘operationalisation’ and evaluation of a single application. This study is placed in a wider context by complementary analyses of other manufacturing users and suppliers of expert systems. The work aims to contribute towards an understanding of expert systems innovation and to improved methodologies for technology assessment and technology transfer.